Characterisation of internal flushing in electrical discharge machining - Gunasekaran, Senthil Kumar (2018)
In this study, Electrical Discharge Machining (EDM) of holes in Inconel 625 and Ti- 6AL-4V alloy using copper and brass tubular electrode is conducted. The effect of volumetric flow rate of dielectric fluid on the various machining characteristics using the copper, brass electrode materials and different work materials are analysed in detail. The machining performance characteristics, namely machining time in sec, electrode wear in mm, surface morphology, discharge gap voltage and current are characterised. This characterisation is handled by varying the state of the internal flushing of the dielectric system. The effect of internal flushing is varied by using the different external diameters of tool electrodes namely 0.8, 1.0, 2.0, and 3.0 mm, subsequently the volumetric flow rate of the dielectric is varied by the varying internal diameters. The surface quality of the fabricated holes are compared using a scanning electron microscope (SEM). From the SEM images, the impact of copper and brass electrode on the surface finish is well understood. Initial experimental study shows that the brass electrodes give rise to a higher material removal than the copper electrode. On the other hand, compare to the brass electrode, copper electrode takes higher machining time but with a lower tool wear, even though it shows effective pulse duration identified in the voltage and current performance curve. The influencing factors, namely work piece materials, electrode materials and volumetric flow rate are statistically analysed using ANOVA approach, on the EDM process responses, namely machining time, electrode wear and surface morphology.